2005
DOI: 10.1158/1078-0432.ccr-04-2672
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Functional B7-H2 and B7.2 Costimulatory Molecules and Their Prognostic Implications inDe novoAcute Myeloid Leukemia

Abstract: Purpose: The B7 family molecules have been shown to regulate immune responses in both positive and negative fashions.Their roles in the progression of human cancers, however, are not well established. The aim of this study was to examine whether leukemic cells of acute myeloid leukemia express functional B7 family molecules and, if so, whether such expression has any clinical significance. Experimental Design: The expression of four B7 family molecules, B7.1, B7.2, B7-H1, and B7-H2, on leukemic cells from acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 44 publications
4
103
1
2
Order By: Relevance
“…Transwell experiments demonstrated that cell contact was required for suppression of proliferation. 24 Previous studies demonstrated that an increase in CD86 expression on malignant cells is associated with a poor prognosis in a variety of malignancies including acute myeloid leukemia and thyroid carcinoma 34,35 ; however, there has been a lack of consensus on the prognostic significance of CD86 in myeloma. 36,37 In murine studies, Sabzevari et al analyzed CD80 levels on T cells after stimulation with APCs and demonstrated various levels of CD80 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Transwell experiments demonstrated that cell contact was required for suppression of proliferation. 24 Previous studies demonstrated that an increase in CD86 expression on malignant cells is associated with a poor prognosis in a variety of malignancies including acute myeloid leukemia and thyroid carcinoma 34,35 ; however, there has been a lack of consensus on the prognostic significance of CD86 in myeloma. 36,37 In murine studies, Sabzevari et al analyzed CD80 levels on T cells after stimulation with APCs and demonstrated various levels of CD80 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings, however, should spur correlative studies to determine the prognostic significance of the differentially expressed genes, and experiments to ascertain whether they play a role in leukemogenesis and could be targeted for therapy. To this end, overexpression of BCL2 in ALL is associated with prolonged survival of leukemic cells 43 and this molecule can be targeted by specific inhibitors 44 ; HSBP1 (heat shock protein 27), CD86 (B7.2), and CD304 (neuropilin-1) overexpression have been associated with drug resistance and disease progression in AML cells [45][46][47] ; expression of CD200 carries an adverse prognosis in patients with multiple myeloma 48 ; and Abs against CD99 and CD123 have been shown to have effective antitumor activity in murine models of Ewing sarcoma 49 and AML, 50 respectively.…”
Section: New All Markers For Mrd 6273mentioning
confidence: 99%
“…In this context, Tamura and coworkers identified an association between low expression of B7-H2 and the escape from immune surveillance indicating that B7-H2 has a potential role in tumorigenesis. B7-H2 [90] is a direct target of miRNA-24, which inhibits B7-H3 expression and therefore is involved in cancer immune evasion. B7-H3 is an immune regulatory molecule, which is often overexpressed in different cancers and associated with metastasis and poor prognosis [91,92].…”
Section: Control Of B7 Family Members By Mirnamentioning
confidence: 99%